Awareness training reduces college students' speech disfluencies in public speaking. Issue 3 (29th April 2019) - Montes, Christina C.; Heinicke, Megan R.; Geierman, Danielle M.
Abstract : Recent research suggests that a modified habit reversal procedure, including awareness training alone or combined with competing response training, is effective in decreasing speech disfluencies for college students. However, these procedures are potentially lengthy, sometimes require additional booster sessions, and could result in covariation of untargeted speaker behavior. We extended prior investigations by evaluating awareness training as a sole intervention while also measuring collateral effects of treatment on untargeted filler words and rate of speech. We found awareness training was effective for all participants without the use of booster sessions, and covariation between targeted filler words and secondary dependent variables was idiosyncratic across participants.